Left Atrial Appendage Thrombus Detected During Hyperacute Stroke Imaging Is Associated With Atrial Fibrillation. Issue 12 (December 2020) - Senadeera, Sajith C.; Palmer, David G.; Keenan, Ross; Beharry, James; Yuh Lim, Jen; Hurrell, Michael A.; Mouthaan, Paul; Fink, John N.; Wilson, Duncan; Lim, Anthony; Wu, Teddy Y.
Abstract : Background and Purpose: Left atrial appendage (LAA) is the likely embolic source in atrial fibrillation (AF)–related cardioembolic strokes. We sought to determine the prevalence of LAA thrombus on hyperacute stroke imaging and its association with AF. Methods: We retrospectively examined the clinical and radiological features of patients assessed through the hyperacute stroke imaging pathway over a 12-month period at Christchurch Hospital. The LAA was included in the computed tomography angiogram scan-range as part of the multimodal imaging protocol. Two radiological readers blinded to clinical information independently assessed for the presence of LAA thrombus. The association between AF and LAA thrombus was determined by multivariable logistic regression analysis. Results: Of 303 patients included in the analysis, the overall prevalence of LAA thrombus was 6.6% and 14.9% in patients with known AF. Patients with LAA thrombus were older (85 versus 75 years, P <0.01), more commonly had known or newly diagnosed AF (75% versus 30%, P <0.01) and heart failure (30% versus 8%, P =0.01), and was associated with intracranial large vessel occlusion (65% versus 39%, P =0.02). In the multivariable model, AF (odds ratio, 3.71 [95% CI, 1.25–11.01] P =0.02) was independently associated with LAA thrombus after adjusting for age and congestive heart failure. Interrater reliability was moderate (kappa=0.56). Conclusions: LAA thrombus is a potential radiological marker of AF and can be assessed as a part of hyperacute stroke imaging. Abstract : Supplemental Digital Content is available in the text.